TINJAUAN TENTANG PELAKSANAAN LELANG ATAS AGUNAN HAK TANGGUNGAN DALAM PERKARA KREDIT MACET ( STUDI PUTUSAN NOMOR 86/PDT/2015/PT.MDN) - suhaila zulkifli zulkifli (jurnal.unprimdn.ac.id, 2018)
Banks as a financial institution in the activities of distributing credit to the public can minimize the risk by applying clear and complete guarantee of the guarantee law, considering that any loan disbursement requires a strong guarantee that serves to guarantee the debtor's debt repayment if the debtor breaches an appointment or bankruptcy. Credit guarantee will provide legal certainty to the bank that the credit will be returned by execution of bank credit guarantee so as to prevent the occurrence of bad loans. The method of research in this writing is the normative juridical which aims to know the provisions of the implementation of the auction against objects of collateral in the credit agreement and to analizes review of decision number 86 / PDT / 2015 / PT-MDN. The legal provisions on the granting of guarantees in credit agreements are regulated in the Codeof civil Law No.4 of 1999 concerning mortgage right, Act No.42 of 1999 on fiduciary guarantee and Law no. 10 Year 1998 About Banking. The provisions of the auction for the objects of collateral in the credit agreement are contained in Article 20 Paragraph (1) Sub-Paragraph a and Sub-Paragraph (2) UUHT and Minister of Finance regulation No.106 / PMK.06 / 2013 About the Auction Guide.